The importance of a forensics investigation of sudden infant death syndrome: recommendations for developing, low and middle income countries - Steven A. Koehler (Acta Medica Academica, 2010)
Sudden infant deaths syndrome (SIDS), the sudden and unexpected death of a normal and healthy infant, has remained a medical and forensic mystery. Despite years of research all attempts to ascertain the exact cause and manner of death have failed. The information collected during the course of the comprehensive investigation by the various investigation agencies and analysis of the data has not been in vain. The epidemiological, demographic, and pathological data have identified distinctive features and risk factors associated with infants that died from SIDS. Epidemiological data has provided the unique characteristics of infants that died of SIDS that differentiates them from non-SIDS infants. Analysis of information from the death scene investigation has identified key risk factor behaviour associated with SIDS, namely the prone sleeping position. Pathological examination of the internal organs, specifically the brain, has shown some differences between SIDS and non-SIDS infants. However, to gain a complete picture of SIDS data, all countries around the world must provide information, even basic information, to understand this syndrome better. Developing countries must understand their role and importance in developing plans to investigate, collect, and disseminate SIDS data to the rest of the world. This paper provides general guidelines for the investigation of SIDS in developing countries.